A Individual Investors’ Interest in Sustainable Stocks in Indonesia: The Roles of Education, Social Media, and Investment Knowledge: The Role of Educational Background, Social Media Influence, and Investment Knowledge - William, Stevan Abraham; Endri, Endri (International Journal of Social and Management Studies, 2025)
This study examines how educational background, social-media exposure, and investment knowledge shape individual investors’ interest in sustainable (ESG) stocks in Indonesia. Using a qualitative design with a small confirmatory survey, data were gathered through purposive and snowball sampling via semi-structured interviews with retail investors (until saturation) and a short online questionnaire; tools included an interview guide, NVivo (QSR International) for thematic coding, IBM SPSS Statistics for basic descriptives and reliability checks, and Google Forms for survey administration, complemented by a desk review of OJK/BEI documents and ESG index fact sheets (IDX ESG Leaders, SRI-KEHATI). Findings indicate that finance-related education aligns with stronger, steadier ESG interest; social media often initiates interest but can induce bias and FOMO, while credible sources and community support sustain it; greater investment knowledge improves content filtering and risk–return judgment, reducing noise from social platforms; investors still prioritize risk, return, and liquidity, with lingering concerns about liquidity and greenwashing; clear ESG labels in trading apps and transparent issuer reporting increase stated intent to invest. Overall, interest peaks when financial and sustainability literacy intersect with credible ESG information and accessible products, yet traditional risk–return–liquidity anchors decisions. Limitations include non-probability sampling, modest sample size, Indonesia-centric context, self-reported data, and a cross-sectional design. The study contributes actionable guidance for regulators, the exchange, platforms, and educators to blend literacy programs, credibility cues, and affordable ESG offerings, and enriches behavioral and sustainable finance by showing how education, social media, and knowledge jointly shape ESG investment intentions in an emerging market.